A Prospective Cohort Study to Evaluate the Impact of Diet, Exercise, and Lifestyle on Fertility: Design and Baseline Characteristics. Issue 11 (30th May 2020) - Mumford, Sunni L; Johnstone, Erica; Kim, Keewan; Ahmad, Mudsar; Salmon, Shanna; Summers, Karen; Chaney, Kayla; Ryan, Ginny; Hotaling, James M; Purdue-Smithe, Alexandra C; Chen, Zhen; Clemons, Traci
Abstract: Diet, lifestyle, and psychosocial factors might influence fertility for men and women, although evidence is mixed, and couple-based approaches are needed for assessing associations with reproductive outcomes. The Impact of Diet, Exercise, and Lifestyle (IDEAL) on Fertility Study is a prospective cohort with contemporaneous detailed follow-up of female partners of men enrolled in the Folic Acid and Zinc Supplementation Trial studying couples seeking infertility treatment (2016–2019). Follow-up of men continued for 6 months, while female partners were followed for 9 months while attempting pregnancy and throughout any resulting pregnancy (up to 18 months). Longitudinal data on diet, physical activity (including measurement via wearable device), sleep, and stress were captured at multiple study visits during this follow-up. A subset of women (IDEALplus) also completed daily journals and a body fat assessment via dual-energy x-ray absorptiometry. IDEAL enrolled 920 women, and IDEALPlus enrolled 218. We demonstrated the ability to enroll women in a prospective cohort study contemporaneous to a partner-enrolled randomized trial. In combination with data collected on male partners, IDEAL data facilitates a couple-based approach to understanding associations between lifestyle factors and infertility treatment outcomes. We describe in detail the study design, recruitment, data collection, lessons learned, and baseline characteristics.